St. Vincent and the Grenadines : Request for Disbursement under the Rapid Credit Facility. (IMF Staff Country Reports; Country Report, 2011)
The Executive Board of the IMF on July 25, 2011, has approved a disbursement of an amount equivalent to SDR 1.245 million under the Rapid Credit Facility (RCF) for St. Vincent and the Grenadines to help the country meet the urgent balance-of-payments need caused by torrential rains, flooding, and landslides in April that caused extensive damage to infrastructure, agriculture, and housing. The RCF, which provides rapid financial assistance for low-income countries with an urgent balance-of-payments need, does not require any program-based conditionality or review.